Xenogeneic Acellular Dermal Matrix for the Treatment of Multiple Gingival Recessions Associated with Partially Restored Noncarious Cervical Lesions - Rossato, Amanda [UNESP]; Mathias-Santamaria, Ingrid Fernandes [UNESP]; Ferreira Ferraz, Lais Fernanda [UNESP]; Gomez Bautista, Cristhian Reynaldo [UNESP]; Viana Miguel, Manuela Maria [UNESP]; Santamaria, Mauro Pedrine [UNESP] (Quintessence Publishing Co Inc, 2022)
This study evaluated the use of a xenogeneic acellular dermal matrix (XADM) combined with a modified coronally advanced flap (MCAF) and partial resin composite filling (anatomic crown plus 1 mm of the root surface) to treat multiple Type 1 gingival recessions associated with B+ noncarious cervical lesions (NCCLs). The study included 24 recessions in 10 patients. Bleeding on probing, probing depth, combined defect height, relative gingival recession, clinical attachment level, esthetics, and dentin hypersensitivity were recorded. After 6 months, the treatment provided statistically significant outcomes: It reduced the combined defect height by 2.02 +/- 0.65 mm, increased clinical attachment level by 1.96 +/- 0.83 mm, and increased keratinized tissue thickness by 0.46 +/- 0.47 mm, and shallow probing depths were seen. Significant dentin hypersensitivity reduction and esthetic improvements were observed. Therefore, XADM associated with MCAF and partial restoration might be a promising alternative to autogenous grafts used to treat multiple gingival recessions associated with B+ NCCLs.